EXPOSITION AND EXEGESIS OF ROMANS 1:3-4: Early Tradition and Pauline, to what Extent? - Adimula, John (Science et Esprit)

(untitled) (Collège universitaire dominicain, Ottawa, 2021)
For many years and still today, the contents of Rom 1:3-4 have attracted a lot of exegetical and theological attention from scholars. There are elements in this pericope that testify to pre-Pauline material, while others are Pauline redactions. In a more precise way, verses 3a and 4e could be regarded as the introduction and concluding parts respectively of this rich formula in 3b-4d. Here (3b-4d), Paul included “in power” and the substantive ἁγιωσύνη as they are already common in his previous letters before Romans (and in Romans), in some cases having a direct link or close usage with the Holy Spirit. The usage of the language of holiness is not only limited to 2 Cor 7:1 and 1 Thess 3:13 but common to other Pauline passages, sometimes expressing that it is the function of the Holy Spirit as the sanctifier (who makes holy).